Recovery of Gold with AgNO3 Pretreatment by Cyanidation at Heap Leaching Cijiwa Gold Ore Processing - Kusdarini, Esthi; Budianto, Agus; Gingga, Flaminggo (UI Scholars Hub, 2018)
This research was undertaken to study the effect of adding silver nitrate (AgNO3) during leaching of gold ore for Aurecovery. Its focus is to obtain the weight of Au in feed and concentrate, the effect of AgNO3 on Au recovery, theconcentration of AgNO3 that led to optimum recovery, and the weight of bullion and Au content in bullion. This research was conducted using quantitative descriptive method with experimental technique and the research stepsinclude the following: 1) rock and treatment plant preparation, 2) tests with variable AgNO3 concentrations, 3) analysis feed and concentrate samples using atomic absorption spectroscopy (AAS), 4) measurement of concentrate density, 5) burning of activated carbon to get the bullion, and 6) weighing bullion and Au content. There was increase Au recovery from 12.57% to 36.15%. On addition of 0 to 4 gram of AgNO3, whereby highest recovery was obtained on the additionof 4 g of AgNO3 concentration to 150 kg of feed.